Study of the Humus Forms in Some Ecosystems of Chakrata Forest (Dehra Dun) U.P., India - Singhal, R. M.; Kumar, Pramod; Sharma, S. D. (Indian Forester, 1987)
Special features of the soil organic materials, present in the forests of Chakrata Himalayas (U.P.) were studied in respect of their nature, distribution and type for the purpose of interpreting their suitability under various forestry management practices. The study indicates that the prevailing favourable conditions of these habitats viz. good aeration, balanced moisture supply, favourable temperature and easily decomposable litter along with fairly good nutrients reserve have given rise to a ’Orthirhizomull’ type of ’Humus form’ which is supposed to contain a stable c1ay-humus aggregations suitable for intensive cultivation and is least susceptilble to ground fires and fertility losses.